1979
DOI: 10.1007/bf03006447
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation and chemoreflexes during enflurane sedation and anaesthesia in man

Abstract: Enflurane sedation and anaesthesia in healthy fit subjects reduced ventilation and the response to carbon dioxide, hypoxaemia and a low dose of doxapram, all in a dose-related fashion. Comparing the three chemoreflexes tested, the response to hypoxaemia and doxapram were the more profoundly impaired; they were nearly totally abolished by anaesthesia. These effects of enflurane on chemoreflex activities are qualitatively similar to those previously observed with halothane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…One of the suggested reasons for the difference in results was that Knill et al [1,2] had used Read's rebreathing method to induce hypercapnia (the end-tidal PCO 2 rises progressively over several minutes as air, or oxygenenriched air, is rebreathed from a large bag), whereas Dahan et al [3] used step hypercapnia (end-tidal PCO 2 rises rapidly to the desired level within seconds). Subsequent studies have explored these observations [4][5][6][7][8][9][10][11][12][13][14]. The original studies of Knill et al [1,2,5,10] found that some agents (N 2 O, enflurane and isoflurane) did indeed depress the ventilation-CO 2 response, but other agents (ether and methoxyflurane), like halothane, had no effect.…”
mentioning
confidence: 99%
“…One of the suggested reasons for the difference in results was that Knill et al [1,2] had used Read's rebreathing method to induce hypercapnia (the end-tidal PCO 2 rises progressively over several minutes as air, or oxygenenriched air, is rebreathed from a large bag), whereas Dahan et al [3] used step hypercapnia (end-tidal PCO 2 rises rapidly to the desired level within seconds). Subsequent studies have explored these observations [4][5][6][7][8][9][10][11][12][13][14]. The original studies of Knill et al [1,2,5,10] found that some agents (N 2 O, enflurane and isoflurane) did indeed depress the ventilation-CO 2 response, but other agents (ether and methoxyflurane), like halothane, had no effect.…”
mentioning
confidence: 99%
“…The observations of Knill et al in the 1970s (since confirmed by many other studies) established that in humans, volatile anaesthetics significantly depress the AHVR [16][17][18]. At low dose (< 0.2 minimum alveolar concentration(MAC)) the degree of depression is …”
Section: Volatile Anaesthetics and Ventilatory Controlmentioning
confidence: 89%
“…It has been reported that tobacco smoke and ammonium vapour increase mucociliary activity and this increase can be partially prevented with atropine and substance P. [31,32] Knill et al showed that halothane and enflurane reduced the peripheral chemoreceptor response to hypoxia and doxapram. [33,34] Coleridge stated that anesthetic agents change the high pulmonary tension and the activity of high-threshold receptors. [35] It has been stated that vagal or sympathetic nerve impulses increase the ciliary beat frequency.…”
Section: Discussionmentioning
confidence: 99%